Real world perspectives on endometriosis disease phenotyping through surgery, omics, health data, and artificial intelligence - Camran R. Nezhat; Tomiko T. Oskotsky; Joshua F. Robinson; Susan J. Fisher; Angie Tsuei; Binya Liu; Juan C. Irwin; Brice Gaudilliere; Marina Sirota; David K. Stevenson; Linda C. Giudice (npj Women's Health)
Abstract Endometriosis is an enigmatic disease whose diagnosis and management are being transformed through innovative surgical, molecular, and computational technologies. Integrating single-cell and other omic disease data with clinical and surgical metadata can identify multiple disease subtypes with translation to novel diagnostics and therapeutics. Herein, we present real-world perspectives on endometriosis and the importance of multidisciplinary collaboration in informing molecular, epidemiologic, and cell-specific data in the clinical and surgical contexts.